Komoditas dalam Skema Request – Offer Indonesia dengan Taiwan: Analisis Inferensia Berdasarkan Database Tahun 2019 - Betrix Betrix; Ferly Christian Kolinug (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Bilateral cooperation between Indonesia and Taiwan has better growth every year, while import tariffs imposed by Taiwan on Indonesia export commodities are still relatively high. This study aims to identify and analyze commodities included in the request-offer scheme between Indonesia and Taiwan based on 2019 database. Identification and analysis of annual growth value, equivalent ad valorem tariff, average export value, export share, average Revealed Comparative Advantage (RCA) index, and RCA trend are carried out through inferential analysis. Inferential analysis is needed to determine the commodities contained in the request-offer scheme of Indonesia and Taiwan that have good performance but are still subject to high import tariffs by their partner countries. Indonesia's export commodities to Taiwan which have a good performance while the import tariffs are still high are given by Taiwan to Indonesia as Indonesia's request scheme to Taiwan, namely: processed food (ofd); tobacco (b_t); vegetables, fruits, and nuts (v_f); and fishery commodities (fsh). Taiwan export commodities to Indonesia that have good performance but are still subject to high import tariffs by Indonesia are Indonesia's offer scheme to Taiwan, namely: manufacturing (lum); cosmetics (crp); miscellaneous edible preparations (ofd); and textiles (tex). Indonesia and Taiwan can increase bilateral cooperation in the field of international trade through barriers lowering schemes and transferring science and technology from each country.